Verhaltensdesign Technologische und ästhetische Programme der 1960er und 1970er Jahre - Moser, Jeannie; Vagt, Christina (Edition Kulturwissenschaft, 2018)
Whether neo-cybernetics, group therapy or environmental protection: an aesthetic-literary and political genealogy of popular education and government programs during the Cold War.